1989
DOI: 10.1007/bf01869151
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of skeletal muscle plasma membrane proteins by calpain

Abstract: Observations described here provide the first demonstration that calpain (Ca2+-dependent cysteine protease) can degrade proteins of skeletal muscle plasma membranes. Frog muscle plasma membrane vesicles were incubated with calpain preparations and alterations of protein composition were revealed by sodium dodecyl sulfate polyacrylamide gel electrophoresis. Calpain II (activated by millimolar concentrations of Ca2+) was isolated from frog skeletal muscle, but the activity of calpain I (activated by micromolar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Both the proteasome and the lysosome are involved in the degradation of the epithelial Na ϩ channel (Staub et al, 1997). In addition, degradation of membrane proteins by calpain has also been reported (Zaidi and Narahara, 1989;Salamino et al, 1994;Ohkawa et al, 1999).…”
Section: Ubiquitination and P-glycoprotein Stability 399mentioning
confidence: 98%
“…Both the proteasome and the lysosome are involved in the degradation of the epithelial Na ϩ channel (Staub et al, 1997). In addition, degradation of membrane proteins by calpain has also been reported (Zaidi and Narahara, 1989;Salamino et al, 1994;Ohkawa et al, 1999).…”
Section: Ubiquitination and P-glycoprotein Stability 399mentioning
confidence: 98%
“…40 Particular attention has been giventothe calciumactivated cysteine protease, calpain, which is known to degrade a wide range of skeletal muscle proteins, including some cytoskeletal and membrane proteins. 41,42 Calpain activity has been shown to be greater in muscles from mdx mice than wild-type mice 43 and it has been reported that the increased calpain activity in mdx mice occurs during periods of both muscle degeneration and regeneration. 44 When the calpain inhibitor,l eupeptin, wasi njected intramuscularly for 30 days, muscle degeneration and necrosis was reduced in mdx muscles by up to 50%.…”
Section: Proteasesmentioning
confidence: 99%
“…It has been shown in vitro that incubating skeletal muscle with calpain produces changes identical to those reported in vivo following exercise (for references, see Belcastro 1993). Other studies have shown that calpain is capable of degrading proteins in skeletal muscle plasma membranes ( Zaidi & Narahara 1989), and that tetanic contractions in isolated frog sartorius muscle lead to a loss of a plasma membrane protein ( Narahara & Green 1983). It is important that calpain I has been found to be activated at Ca 2+ concentrations as low as 1 μ M ( Belcastro 1993) or 5 μ M ( Dayton et al .…”
Section: Ca2+‐induced Cell Damage As a Vicious Cyclementioning
confidence: 99%